Indirect Effects of Current Velocity on Algal Abundance Through Interactions with Ceratopsyche Larvae - Rutter, Sarina (My University, 2013)
Stream current velocity has been shown to affect the distribution of benthic organisms in direct and indirect ways. The purpose of this study was to test the hypotheses: If the indirect relationship between current velocity, Ceratopsyche and algal abundance was important, the following would be shown: 1) a positive correlation between current velocity and Ceratopsyche density; 2) a negative correlation between Ceratopsyche density and algal abundance; and 3) a negative correlation between current velocity and algal abundance.
Color poster with text, images, photographs, graphs, and charts.
Keywords: Stream current velocity; Algal abundance; Ceratopsyche larvae density; Posters